Autores - Rivas, Ramón D. (Kóot, 2017)
Chester Urbina Gaitán Ernesto Rivas Arévalo Héctor Samour Dr. Jorge Alberto Amaya Banegas Julián Barrera Tolentino Elisa Pritzker Sigfredo Cabrera Rajo Rubén Fúnez Ramón D. Rivas Julio Martínez Mario Bencastro